Orderability, contact non-squeezing, and Rabinowitz Floer homology - Albers, Peter; Merry, Will J. (Arxiv, 2014)
We study Liouville fillable contact manifolds ([Sigma,Xi]) with non-zero Rabinowitz Floer homology and assign spectral numbers to paths of contactomorphisms.
Gesehen am 28.02.2019